Toward hospital resilience: a qualitative study on the identification of hospital shocks during disruption era in Indonesia - Nurmala Sari; Mayeh Omar; Syahrir A Pasinringi; Andi Zulkifli; Andi Indahwaty Sidin; Irwandy Irwandy; Yahya Thamrin; Lalu Muhammad Saleh; Dumilah Ayuningtyas (BMC, 2024)
Abstract Background Hospital resilience has been well recognized among healthcare managers and providers as disruption of hospital services that threatens their business environment. However, the shocks identified in the recent hospital resilience concept are mainly related to disaster situations. This study aims to identify potential shocks that hospitals face during disruptions in Indonesia. Method This qualitative study was conducted in Makassar, Indonesia in August-November 2022. Data was collected through semi-structured interviews with hospital managers and resilience experts using a semi-structured interview guide. 20 key informants were interviewed and data were analyzed by thematic analysis. Results The study identified seven shocks to hospitals during the disruption era: policy, politics, economics, hospital management shifting paradigms, market and consumer behavior changes, disasters, and conflicts. It also identified barriers to making hospitals resilient, such as inappropriate organizational culture, weak cooperation across sectors, the traditional approach of hospital management, inadequate managerial and leadership skills, human resources inadequacies, a lack of business mindset and resistance to change. Conclusion This study provides a comprehensive understanding of hospital shocks during disruptions. This may serve as a guide to redesigning the instruments and capabilities needed for a resilient hospital.